Penguatan Nilai Aqidah dan Akhlak Anak Usia Dini Melalui Pertunjukan Drama Islami: Studi Pengabdian di BA Aisyiyah Ngombakan, Sukoharjo - 'Ilmi Azizah, Annafi' Nurul; Pratama, Syafi Widiya; Rahmadani, Amelya Puspita; Aghaariid, Luthfi Haniifah; Sakina, Salma; Al- Fara, Nayla Jasmine; Berliana, Nuke Intan (CV. Devi Tara Innovations, 2025)
This community service activity aims to instill and strengthen the values of faith and morals in early childhood through the media of Islamic drama performances entitled